E-Modules to Improve Learning Independence, Motivation and Learning Outcomes - Tumiar Sidauruk; Delita, Fitra; Nurmala Berutu; Elfayetti; Rohani (LPPM Undiksha, 2025)
Digital-based teaching materials such as e-modules are a necessity for learning resources that can improve learning processes and outcomes. However, the development of e-module is still limited in lectures, especially in the Geography Education Department, FIS Unimed. The aim of this research is to develop an e-module, measure its feasibility and describe its effect on learning independence, motivation and learning performances. This study used the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). A quasi-experimental research design was carried out to measure the effect of using e-modules. The population in this study were students in the fourth semester of the Geography Education Department, FIS Unimed, consisting of 4 classes. Random sampling by lottery was used to obtain class samples. Class A as the control class (20 students) and Class C as the experimental class (20 students). An online questionnaire was used to collect data on learning independence and motivation. Meanwhile, tests are used to collect learning performance data. Descriptive statistics and inferential statistics were performed for data analysis. The statistical tests carried out were t-test and ANCOVA. The research findings showed that the e-module was very feasible for use in lectures based on validation from a team of experts through 2 stages. The implementation of e-modules in lectures can significantly enhance learning independence, motivation and learning performance. Therefore, modules as the main learning resource need to be developed on an electronic resources (e-modules) so that e-modules easily accessible to students.